Quality certification for nonprofits, charitable giving, and donor's trust: Experimental evidence - Maja Adena; Jeyhun Alizade; Frauke Bohner; Julian Harke; Fabio Mesters (Journal of Economic Behavior & Organization, 2019)
In an experiment, we test the impact of quality certificates on donations to a charity. Compared to the control group, participants presented with a quality certificate chose higher donations by around 10% and reported higher trust in the same charity. The choice of donation values over time shows strong persistence such that the difference between the two groups remained even after all participants were informed about the certificate. Since the initially uninformed donors did not adjust their donations upwards to a sufficient extent, we conclude that quality certification is less likely to affect giving by existing donors. Finally, we find no significant negative effect of information about certificate fees.
doi:10.7802/1.2121
Keywords: D64; C99; D81; 330; nonprofit certification; charitable giving; experiment; trust